Kesiapan Pelaku Usaha Terhadap Implementasi Program Sertifikasi Halal Gratis (SEHATI) - Maharani, Taradiva; Suma, Nasobi Niki (Fakultas Dakwah UIN KHAS Jember, 2023)
Islamic orders recommend consuming halal and good food. Based on this, it is important for Muslims to ensure that the food and products they consume are halal. The Free Halal Certification Program (SEHATI) for 2022 until now is the government's effort to guarantee halal products to the public by seeking halal education and socialization carried out by the Halal Product Assurance Organizing Agency (BPJPH) under the auspices of the Ministry of Religion. Law Number 33 of 2014 concerning Guarantees for Halal Products and Government Regulation Number 9 of 2021 concerning Implementation of the JPH Field give authority and responsibility to BPJPH to guarantee halal products circulating, entering and trading in Indonesia. However, there are several obstacles faced by extension agents in the field of Free Halal Certificates in Giri District. Among them: lack of public interest in registering, lack of public awareness about the importance of using halal certificates, and public trust in sustenance ,which is one of the obstacles/challenges in achieving the targets of the SEHATI program. The purpose of this reseach has to find out how much the UMK Giri District has prepared for the SEHATI Program organized by the Government. The research method uses descriptive qualitative research involving observation and interviews. The results of the reseach show that the readiness of Giri UMK actors for the SEHATI program is very low and they do not realize the importance of the Halal label in every product they produce.